2019
DOI: 10.3390/cli7070086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Infilling Methods for Time Series of Daily Temperature Data: Case Study of Limpopo Province, South Africa

Abstract: Incomplete climate records pose a major challenge to decision makers that utilize climate data as one of their main inputs. In this study, different climate data infilling methods (arithmetic averaging, inverse distance weighting, UK traditional, normal ratio and multiple regression) were evaluated against measured daily minimum and maximum temperatures. Eight target stations that are evenly distributed in Limpopo province, South Africa, were used. The objective was to recommend the best approach that results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The present study was performed at Zuurfontein farm in Polokwane. The temperature in winter ranges from 7°C to 21°C and in summer ranges from 16°C to 28.1°C and experiences an annual rainfall of more than 600 mm [15].…”
Section: Study Period and Areamentioning
confidence: 99%
“…The present study was performed at Zuurfontein farm in Polokwane. The temperature in winter ranges from 7°C to 21°C and in summer ranges from 16°C to 28.1°C and experiences an annual rainfall of more than 600 mm [15].…”
Section: Study Period and Areamentioning
confidence: 99%
“…The NR method was selected so as to estimate the missing daily precipitation and daily temperature values since similar studies have found that it outperformed other daily rainfall infilling methods during the use of two to five index gauges (Mair and Fares, 2010 ). It is also a recommended infilling method for timeseries of daily temperature data (Shabalala et al 2019 ) and is expressed as follows: where P x is the missing value of precipitation or temperature at meteorological station x , P i is the observed precipitation or temperature value for the same period at the ith neighbouring station, N x is the normal annual precipitation or temperature of the station x , N i is the normal annual precipitation or temperature of the ith station and n is the number of neighbouring stations. Moreover, the Milos M.S.…”
Section: Study Area and Description Of Datasetsmentioning
confidence: 99%
“…The NR method was selected so as to estimate the missing daily precipitation and daily temperature values since similar studies have found that it outperformed other daily rainfall infilling methods during the use of two to five index gauges (Mair and Fares, 2010). It is also a recommended infilling method for timeseries of daily temperature data (Shabalala et al 2019) and is expressed as follows:…”
Section: Study Area and Description Of Datasetsmentioning
confidence: 99%
“…Furthermore, erroneous, suspicious and impossible values were patched using good quality data from nearby weather stations (within a radius of 100 km) to obtain complete long-term data sets of good quality. An inverse distance weighting method was used to estimate missing or erroneous daily rainfall and RH from neighbouring station data based on the recommendations of Moeletsi et al 30 The multiple regression method was used to estimate missing or erroneous T air min , T air max and U values from neighbouring station data based on the recommendations of Shabalala et al 34 The Hargreaves-Samani equation was used to estimate missing or erroneous daily R s from measurements of T air min and T air max based on the recommendations of Abraha and Savage 35 .…”
Section: Climate Datamentioning
confidence: 99%